Android-based Mobile Information System Design For Rehabilitated And Released Animals At The Natural Resources Conservation Center In Bengkulu City - Handrajati, Muhammad Sultan; Utami , Feri Hari; Sapri , Sapri (Jurnal Komputer Indonesia, 2022)
The Mobile Information System is one of the information management systems whose development is very fast along with the increasing development of human intelligence. In its development, what is needed to develop a Mobile Information System is data and information. Mobile Information System is very important for the development of an agency. One of them is the Mobile Information System on rehabilitated and released animals at the Bengkulu City BKSDA. In this study, an application was developed by implementing a Mobile Information System that was able to display data on rehab and released animals, and also the basis of this application there were two types, namely Android and Web. This Mobile Information System is divided into two application parts, namely android-based applications and web-based applications. For data processing using an android application, while for information about animal rehabilitation reports and released animals can use a web-based application..